Unreal Engine Based MCS Program Using Microcontroller Wemos D1 Mini, MPU-9250 Sensor and UDP Protocol - Simatupang, Frengki; Manalu, Istas Pratomo (Piston: Journal of Technical Engineering, 2024)
The Motion Capture System (MCS) is a series of steps involving the capture, processing, and mapping of human, animal, or object movements into virtual characters. This process includes motion recording, data processing with computers, and mapping the results into digital models. This article discusses the use of MCS for realistically reconstructing and simulating behavior, which is valuable in various applications such as entertainment, animation, computer games, sports, and rehabilitation. MCS faces challenges in accurately capturing the diversity and complexity of body movements, requiring advanced hardware and software. Unreal Engine, a development platform known for its ability to produce high-quality graphics and realistic physics systems, is often used to integrate MCS. The MPU9250 sensor, a 9-axis inertial sensor combining an accelerometer, gyroscope, and magnetometer, is used in this project to detect linear motion, rotation, and orientation with high accuracy. This research aims to develop an MCS program based on Unreal Engine using the MPU9250 sensor and the UDP protocol, with the Wemos D1 Mini as the client module to process and transmit sensor data via Wi-Fi. This process involves collecting sensor data, transmitting data via UDP, and processing the data in Unreal Engine to control the movement of objects or characters. Sensor calibration is performed to obtain accurate reference values, and the collected data is used to calculate pitch, roll, and yaw values. This data is then sent to Unreal Engine to display animations corresponding to human movements. Testing shows that the generated movements align with those demonstrated, although there are minor acceptable errors. This research highlights the importance of combining sensor technology and software to produce an accurate and responsive motion control system, providing an interactive and realistic user experience.